Faktor Keberhasilan Kritis Usaha Kuliner Berbasis Cloud Kitchen Dari Perspektif Pelaku Usaha dan Konsumen - Sugiarto, Christian Ryan; Lastiawan, Joey Prakarsa; Yunus, Erlinda Nusron (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Cloud kitchen is a food service business system that does not serve dine-in orders and only focuses on serving delivery. This study aims to identify the characteristics, challenges, and critical success factors of cloud kitchen-based culinary businesses. Critical success factors will be analyzed from the point of view of cloud kitchen’s tenants as well as from the consumer's point of view. The research method used is the mixed method. The research begins with a qualitative method, employing phenomenology approach. Characteristics found in the study were low cost, simpler operational activities, and unique branding. The challenges are dependency on the aggregator, profit margin, voice of customer, and branding. Meanwhile, the critical success factors identified in the study are sales promotion, food taste, brand reputation, online rating, packaging, and hygiene. Then, the research is continued by distributing questionnaires to determine the critical success factors from the consumer's perspective as the independent variable, repurchase intention as the dependent variable, and customer satisfaction as the intervening variable. The results showed a significant influence on repurchase intention of all critical success factors mediated by customer satisfaction. Critical success factors also affect repurchase intention directly except for the hygiene factor. Meanwhile, the importance of critical success factors according to the consumer's point of view from the most important factors are food taste, sales promotion, brand reputation, rating in applications, food hygiene, and product packaging. Keywords: cloud kitchen, characteristics, challenges, CSF, Mix Method